Polar Organic Pollutants in Groundwater: Experimental Approaches to Biodegradation During Subsoil Passage - T.P. Knepper (The Scientific World Journal)
A selection of polar organic compounds was investigated for their biodegradation on a laboratory scale fixed-bed bioreactor and the decline of the parent compounds besides the formation of metabolites was monitored. Of particular interest was the investigation into the degradation of pesticides, especially isoproturon (IPU), surfactants and industrial by-products of chemical synthesis. The results from the laboratory degradation experiments are compared to findings in groundwater.